The usage of TiO2@Fe3O4 nanocomposites synthesized by a novel and facile method as adsorbents in the separation/preconcentration of silver ions from domestic wastewater samples - Hilal Akbiyik; Ayça Girgin; Buse Tuğba Zaman; Arda Atakol; Nevim San; Sezgin Bakirdere (Journal of Analytical Science and Technology, 2025)
Abstract Global population growth has led to an increase in the consumption of silver, which has a wide range of applications. This situation has increased demand for determining trace levels of silver to protect public health and the environment. In this study, an efficient magnetic-dispersive solid phase extraction (MDSPE) method was developed utilizing TiO2@Fe3O4 nanocomposites (NCs) as adsorbent for the separation and preconcentration of silver ions. TiO2 nanoparticles (NPs) were synthesized by a microwave-assisted hydrothermal method under different precursor solution and temperature program conditions. The procedure yielding TiO2 NPs with the homogeneous size distribution was established, and the NPs obtained with this procedure were used to modify the Fe3O4 surface. TiO2@Fe3O4 NCs and TiO2 NPs synthesized via alternative innovative methods to traditional techniques were examined by various characterization methods. Flame atomic absorption spectrometry (FAAS) was used for detection and quantification of analyte. All parameters expected to affect the adsorption and desorption of silver ions on the TiO2@Fe3O4 NCs were optimized. In the developed procedure, the optimum parameters were 20 mg TiO2@Fe3O4 NC, 1.5 mL potassium hydrogen phthalate buffer solution (pH 6.0), orbital agitation for 30 min, and 0.10 mL HNO3 (2.0 M). The proposed novel TiO2@Fe3O4-MDSPE-FAAS method exhibits detection and quantification limits of 0.005 and 0.017 mg kg−1 in a wide linear working range for silver ions. The method’s relevance and accuracy were evaluated by recovery experiments conducted on both actual and synthetic residential wastewater samples, yielding satisfactory percent recovery results using a matrix-matching calibration strategy. Graphical abstract